The complement alternative pathway in paroxysmal nocturnal hemoglobinuria: From a pathogenic mechanism to a therapeutic target. Issue 1 (15th September 2022) - Risitano, Antonio M.; Frieri, Camilla; Urciuoli, Eleonora; Marano, Luana
Summary: Paroxysmal nocturnal hemoglobinuria (PNH) is a rare clonal, not malignant, hematological disease characterized by intravascular hemolysis, thrombophilia and bone marrow failure. While this latter presentation is due to a T‐cell mediated auto‐immune disorder resembling acquired aplastic anemia, the first two clinical presentations are largely driven by the complement pathway. Indeed, PNH is characterized by a broad impairment of complement regulation on affected cells, which is due to the lack of the complement regulators CD55 and CD59. The deficiency of these two proteins from PNH blood cells is due to the somatic mutation in the phosphatidylinositol N‐acetylglucosaminyltransferase subunit A gene causing the disease, which impairs the surface expression of all proteins linked via the glycosylphosphatidylinositol anchor. The lack of the complement regulators CD55 and CD59 on PNH erythrocytes accounts for the hallmark of PNH, which is the chronic, complement‐mediated intravascular hemolysis. This hemolysis results from the impaired regulation of the alternative pathway upstream in the complement cascade, as well as of the downstream terminal pathway. PNH represented the first indication for the development of anti‐complement agents, and the therapeutic interception of the complement cascade at the level of C5 led to remarkable changes in the natural history of the disease. Nevertheless, the clinical use of an inhibitor of the terminal pathway highlighted the broader derangement of complement regulation in PNH, shedding light on the pivotal role of the complement alternative pathway. Here we review the current understanding of the role of the alternative pathway in PNH, including the emergence of C3‐mediated extravascular hemolysis in PNH patients on anti‐C5 therapies. These observations provide the rationale for the development of novel complement inhibitors for the treatment of PNH. Recent preclinical and clinical data on proximal complement inhibitors intercepting the alternative pathway with the aim of improving the treatment of PNH are discussed, together with their clinical implications which are animating a lively debate in the scientific community.